5(2x+6)-2x=8(x+5)

Simple and best practice solution for 5(2x+6)-2x=8(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x+6)-2x=8(x+5) equation:


Simplifying
5(2x + 6) + -2x = 8(x + 5)

Reorder the terms:
5(6 + 2x) + -2x = 8(x + 5)
(6 * 5 + 2x * 5) + -2x = 8(x + 5)
(30 + 10x) + -2x = 8(x + 5)

Combine like terms: 10x + -2x = 8x
30 + 8x = 8(x + 5)

Reorder the terms:
30 + 8x = 8(5 + x)
30 + 8x = (5 * 8 + x * 8)
30 + 8x = (40 + 8x)

Add '-8x' to each side of the equation.
30 + 8x + -8x = 40 + 8x + -8x

Combine like terms: 8x + -8x = 0
30 + 0 = 40 + 8x + -8x
30 = 40 + 8x + -8x

Combine like terms: 8x + -8x = 0
30 = 40 + 0
30 = 40

Solving
30 = 40

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -4/17(17/8) | | -5(-2-8m)=10+5m | | x+3=1.34x | | 45+13x=4x+9(5+x) | | 2a-4+-3-7= | | 8n(3n+8)= | | S-7=-10 | | 7/8y=-21 | | 11/9=21-15 | | -8z+12=60 | | c^2+18c+81-q^2= | | 8=m/-3 | | 76=-9k+4 | | -2(v-2)=-3-2v | | 6+5a-122(6+84-6x)-75*45x= | | 11c+6whenc=-3 | | 3(6x-4)+2(3x-3)= | | bx+6=dx+3 | | Sinx=14/23 | | 1=y-(3/2)x | | 3tanx-3=5tanx | | 36+8x=5(5x-5)-7 | | y/3=69 | | 8x+2(-5x-4)=-12 | | w/2=44 | | 360=16x-4+16x-4+14x+34+14x+34 | | 12x+9=75 | | -120=-12x | | 5x-12.3=2x+9 | | 105=8p+9 | | a^2+18a+40=-5 | | 36-7p=-7(p-5) |

Equations solver categories